2019
DOI: 10.1371/journal.pone.0224928
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ASVS for insulinoma localization: A systematic review and meta-analysis

Abstract: BackgroundPrevious studies on the diagnostic value of arterial calcium stimulation with hepatic venous sampling (ASVS) for the localization of insulinoma have reported inconsistent results. Here, we performed a meta-analysis of the relevant published studies.MethodsPubMed, Embase, Web of Science, the Cochrane Library, and Wanfang Data were searched for studies on the diagnostic value of ASVS in insulinoma localization published up to May 2019. We calculated the sensitivity, specificity, positive likelihood rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…EUS and ASVS are invasive techniques to localize insulinoma when the non-invasive techniques fail, and the suspicion remains high. EUS has a sensitivity of up to 89%, whereas the sensitivity of ASVS has been reported to be up to 93% (5,6). Patel et al reported 2 cases of insulinomas with negative imaging (including negative octreotide scan in one case).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EUS and ASVS are invasive techniques to localize insulinoma when the non-invasive techniques fail, and the suspicion remains high. EUS has a sensitivity of up to 89%, whereas the sensitivity of ASVS has been reported to be up to 93% (5,6). Patel et al reported 2 cases of insulinomas with negative imaging (including negative octreotide scan in one case).…”
Section: Discussionmentioning
confidence: 99%
“…Several non-invasive techniques are used to localize the lesion and include an ultrasound (US) abdomen, CT scan, MRI, and molecular imaging techniques like NM 18F-DOPA whole-body PET CT and Ga-68 DOTATATE scan (2)(3)(4). Due to the low sensitivity of the non-invasive methods, the localization of the tumor presents a diagnostic challenge, and invasive techniques like endoscopic ultrasound (EUS) and angiography and arterial stimulation venous sampling (ASVS) should be used if the suspicion is high (5,6). We present a case of insulinoma presenting with seizure episodes.…”
Section: Introductionmentioning
confidence: 99%
“…After biochemical confirmation of insulinoma, medical imaging is recommended. An intraoperative ultrasound has a very high positive detection rate, however revealing the insulinoma before a surgery treatment makes surgery easier [3,7]. The small size of insulinomas challenges the detectability by conventional imaging techniques like contrastenhanced CT and contrast enhanced MRI beacause of motion artifacts.…”
Section: Description Of the State Of Knowledge About Diagnosticmentioning
confidence: 99%
“…On the other hand, an endoscopic ultrasound is invasive technique and the visualisation of pancreas is not always possible. It has a positive rate of 80-89%, depending on the operator's technique and experience [7]. The selective arterial calcium stimulation test with hepatic venous sampling (SACST) is used when the preoperative localization of insulinomas by previous techniques is not possible.…”
Section: Description Of the State Of Knowledge About Diagnosticmentioning
confidence: 99%
See 1 more Smart Citation